Ischaemic risk and efficacy of ticagrelor in relation to time from P2Y12 inhibitor withdrawal in patients with prior myocardial infarction: insights from PEGASUS-TIMI 54 - Bonaca, Marc P; Bhatt, Deepak L; Steg, P Gabriel; Storey, Robert F; Cohen, Marc; Im, Kyungah; Oude Ophuis, Ton; Budaj, Andrej; Goto, Shinya; López-Sendón, José; Diaz, Rafael; Dalby, Anthony; et al. (European heart journal, 2016)
Ticagrelor reduced major adverse cardiovascular event (MACE) by 15-16% in patients with prior myocardial infarction (MI) in PEGASUS-TIMI 54. We hypothesized that patients who recently discontinued P2Y12 inhibition, even years after MI, may be at particular risk of MACE and may derive particular benefit from continuation or reinitiation of therapy. Patients in PEGASUS-TIMI 54 were categorized by time from last P2Y12 inhibitor (days: ≤30, >30-360, >360). The risk of MACE and the efficacy of ticagrelor were compared across categories. In the placebo arm, patients who more recently stopped P2Y12 inhibitor therapy had a greater number of risk factors but still had a higher risk of MACE after multivariable adjustment [≤30 days, hazard ratio (HR)adj 1.47, 95% confidence interval (CI) 1.12-1.93, P = 0.0051; 30 days-1 year, HRadj 1.28, 95% CI 0.98-1.67, P = 0.073] compared with those who stopped >1 year prior (P-trend = 0.0097). The benefit of ticagrelor depended on the time from last dose, with HRs (95% CI) for ticagrelor (pooled doses) vs. placebo of 0.73 (0.61-0.87), 0.86 (0.71-1.04), and 1.01 (0.80-1.27), respectively, by category (P-trend for interaction < 0.001). The benefit in those ≤30 days of stopping was similar regardless of time from MI (<2 years, HR 0.73, 95% CI 0.60-0.89 vs. ≥2 years, HR 0.71, 95% CI 0.50-1.00). The benefit of ticagrelor for long-term secondary prevention in patients with prior MI and at least one additional risk factor appeared more marked in patients continuing on or re-starting after only a brief interruption of P2Y12 inhibition, when compared with patients who had proved themselves stable more than 2 years from their MI and off P2Y12 inhibitor therapy for more than a year. The increase in bleeding events with ticagrelor was similar regardless of this time interval. For clinicians considering a strategy of prolonged P2Y12 inhibitor therapy in high-risk patients, these data suggest greater benefit in the continuation of such therapy without interruption after MI, rather than re-initiating such therapy in patients who have remained stable for an extended period. Future analyses may help to clarify further the profile of post-MI patients most likely to benefit from uninterrupted dual antiplatelet therapy. http://www.clinicaltrials.gov NCT01225562.